Peningkatan Kemampuan Membaca Permulaan Menggunakan Media Papan Flanel Cerdas pada Anak Didik Usia 5 – 6 Tahun - Sari, Evi Purwita; Wijaya, Intan Prastihastari; Dwiyanti, Linda (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to improve initial reading skills in group B students at Dharma Wanita Kindergarten, Jambi Village. This study used the PTK approach, with the research subjects being group B students of the Dharma Wanita Kindergarten, Jambi Village. The research was conducted in 3 cycles, using observation sheet instruments, performance or worksheets, and documentation. The results of this study show that (1) Through the learning action cycle, it can be proven that children who were previously not fluent in reading skills are now fluent (2) after researching, children who previously did not memorize letters now have memorized (3) Through action cycles Learning smart Flanel board media is proven to be able to improve reading comprehension skills for students who previously felt bored because of the teacher's lack of creativity in learning media, now children are more enthusiastic when participating in learning activities. It can be shown through the results of the mastery cycle in learning using smart Flanel board media that has been carried out, namely in cycle I getting a percentage of 41.16%, cycle II 70.58%, and cycle III 94.11%, which can be said to have increased as expected.